PENGARUH MODEL PEMBELAJARAN QUANTUM TEACHING DENGAN LANGKAH-LANGKAH TANDUR TERHADAP KETERAMPILAN PROSES BELAJAR SISWA MATERI SEL KELAS XI DI SMA MUHAMMADIYAH 1 PALEMBANG - Muhammad Isnaini; Indah Wigati; halimatus syadiyah (Bioilmi: Jurnal Pendidikan, 2016)
This research entitled "The Influence of Learning Quantum Teaching Model With Tandur Steps on The Skills Student Learning Cells Material for XI grades In Senior High School of Muhammadiyah 1 Palembang" This research was motivated by a teacher-centered learning model. This consequent of this model, was the learning takes place in one direction and the students have less opportunity to see the real phenomenon or media related material. The fact indicates that the methods used by teachers in teaching is dominated by the use of conventional methods. The purpose of this study was to determine the effect of quantum teaching model with measures against graft in Process Skills on Sel Material. The sample was a class XI 2 with 30 students and class XI 3 with 30 students. Methods of data collection using performance assessment. The analysis of the data used is a statistical test by using a statistical formula t test. The df = 58, a significant level of 0.05 for t-table value of 1.672 while the value t count of 5,433. The analysis mean is an effect of the quantum teaching model on the students learn skill for cell material in grades XI Senior High School of Muhammadiyah 1 Palembang.